3D printed hydrogel/wesselsite-PCL composite scaffold with structural change from core/shell fibers to microchannels for enhanced bone regeneration. (November 2022) - Dong, Chao; Wei, Hao; Zhang, Xiaonan; Li, Yuxiao; Huang, Lifei; Wa, Qingde; Luo, Yongxiang
Abstract: Corresponding to the process of bone formation, three-dimensional (3D) scaffolds should provide adaptive structural cues and microenvironment for bone repair at different stages. Herein, we fabricate a core-shell fiber scaffold by coating a layer of polycaprolactone (PCL)/SrCuSi4 O10 (wesselsite, CS) on 3D printed hydrogel scaffolds. The core/shell scaffold provided enhanced mechanical support for the defect at the initial stage. Then, the degradation of hydrogels resulted in the transformation of core/shell fiber structure (hydrogel/PCL + CS) to interconnected microchannels (PCL/CS hollow channel), which provided increasing space and clear architectural cues for promoting bone formation and vascularization. Simultaneously, the chemokine stromal cell-derived factor-1α (SDF-1α) loaded in hydrogels achieved sustained release in the initial two weeks to facilitate the recruitment of bone marrow stromal cells (BMSCs) to defect. Subsequently, the degradation of CS nanomaterials yielded the sustained release of bioactive ions (Si, Sr and Cu), promoting osteogenesis and angiogenesis. The in vivo data showed that the prepared scaffolds exhibited enhanced bone repair capacity with abundant new bone formation and blood vessels ingrowth in the defect. Thus, this designed system shows great potential for bone tissue engineering application.